A Narrative Study of Qualitative Data on Sexual Assault, Coercion and Harassment - Cairns, Kathleen V. (Canadian Journal of Counselling and Psychotherapy, 2007)
A narrative analysis of 159 stories of unwanted sexual attention written bv residents in single student residence halls is provided. Four story types are reviewed with separate consideration of the contributions of female and male residents. The patterns of sexual harassment in residence and their consequences for residents are described and discussed with particular reference to the implications for counselling and recommendations concerning the content and process of preventive education.